Photopolymerization kinetics of block polyether based terminal urethane methacrylate with/without cross-linker - Reghunathan, Harikrishna (Advances in Polymer Technology, 2014)
The present work deals with the photopolymerization of difunctional macromonomer with a polyether chain and urethane methacrylate terminations. Macromonomeric formulations were prepared by mixing macromonomer with two different concentrations of photoinitiator. Formulations were also prepared by the addition of 10 wt% of soft-segmented difunctional cross-linker to the abovementioned macromonomic formulations. All formulations were then subjected to photopolymerization studies and the effects of light intensity on the photopolymerization kinetics were studied at two different isothermal conditions using photo differential scanning calorimetry (Photo DSC) with polychromatic radiation. The isothermal heat flow against time was recorded for all formulations and the kinetic parameters were noted. It was observed that the rate of maximum polymerization as well as peak maximum time showed a general trend. However, the ultimate conversion as well as the conversion at maximum rate did not show any trend due to diffusional restrictions imparted by the increase in viscosity with conversion. The photopolymerization of the formulations and curing kinetics including evaluation of autocatalytic model are discussed. (C) 2014 Wiley Periodicals, Inc.
Keywords: kinetics; Macromonomers; Modeling; Photo DSC; Photopolymerization